Extracorporeal treatment for calcium channel blocker poisoning: systematic review and recommendations from the EXTRIP workgroup. (4th May 2021) - Wong, Anselm; Hoffman, Robert S.; Walsh, Steven J.; Roberts, Darren M.; Gosselin, Sophie; Bunchman, Timothy E.; Kebede, Sofia; Lavergne, Valery; Ghannoum, Marc; ,; Alhatali, Badria; Anseeuw, Kurt; et al.
Abstract: Background: Calcium channel blockers (CCBs) are commonly used to treat conditions such as arterial hypertension and supraventricular dysrhythmias. Poisoning from these drugs can lead to severe morbidity and mortality. We aimed to determine the utility of extracorporeal treatments (ECTRs) in the management of CCB poisoning. Methods: We conducted systematic reviews of the literature, screened studies, extracted data, summarized findings, and formulated recommendations following published EXTRIP methods. Results: A total of 83 publications (6 in vitro and 1 animal experiments, 55 case reports or case series, 19 pharmacokinetic studies, 1 cohort study and 1 systematic review) met inclusion criteria regarding the effect of ECTR. Toxicokinetic or pharmacokinetic data were available on 210 patients (including 32 for amlodipine, 20 for diltiazem, and 52 for verapamil). Regardless of the ECTR used, amlodipine, bepridil, diltiazem, felodipine, isradipine, mibefradil, nifedipine, nisoldipine, and verapamil were considered not dialyzable, with variable levels of evidence, while no dialyzability grading was possible for nicardipine and nitrendipine. Data were available for clinical analysis on 78 CCB poisoned patients (including 32 patients for amlodipine, 16 for diltiazem, and 23 for verapamil). Standard care (including high dose insulin euglycemic therapy) was not systematically administered. Clinical data did not suggest an improvement in outcomes with ECTR. Consequently, the EXTRIP workgroup recommends against using ECTR in addition to standard care for patients severely poisoned with either amlodipine, diltiazem or verapamil (strong recommendations, very low quality of the evidence (1D)). There were insufficient clinical data to draft recommendation for other CCBs, although the workgroup acknowledged the low dialyzability from, and lack of biological plausibility for, ECTR. Conclusions: Both dialyzability and clinical data do not support a clinical benefit from ECTRs for CCB poisoning. The EXTRIP workgroup recommends against using extracorporeal methods to enhance the elimination of amlodipine, diltiazem, and verapamil in patients with severe poisoning.